Strategi Badan Amil Zakat Desa Dalam Meningkatkan Kesadaran Masyarakat Untuk Membayar Zakat Mal (Studi Kasus Bazdes Mampun Baru) - Sawitri Kurniasih; Arsa Arsa; Ferri Saputra Tanjung (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Zakat is an obligation that must be carried out by every Muslim for his property and objects with the rules that have been determined in Islamic law. Mapun Baru Village has a large potential for zakat mal, therefore in order to maximize its potential it requires good management and a good strategy to increase public awareness in carrying out zakat mal payments. The purpose of this study was to find out 1) the strategy carried out by BAZDES in raising public awareness to pay zakat mal, 2) find out the causes of reduced public awareness to pay zakat mal. The research method used by researchers is qualitative. The type of data used by researchers is primary data and secondary data. With this research method, researchers see the object of research directly by conducting field observations and conducting interviews with BAZDES administrators, people who pay zakat, people who pay zakat directly to mustahik, and people who do not pay zakat mal. Furthermore, secondary data such as data, journals, and books related to research. The results of this study were 1) strategies implemented by BAZDES management in the form of socialization, cults after congregational prayers and after yasinan, and working with preachers when giving lectures. 2) the cause of the low public awareness to pay zakat is in the form of knowledge of people's understanding that is still minimal about the scope of zakat mal.